Determination of Tannin in Ethanol Extract of Bajakah Tampala Root (Spatholobus littoralis Hassk) as an Anticholesterol - Saskia, Eka Putri; Tahir, Masdiana; Suhaenah, Asriani (Universitas Muslim Indonesia, 2025)
The root of Bajakah Tampala (Spatholobus littoralis Hassk.) is known to contain several bioactive secondary metabolites, including saponins, flavonoids, phenolics, and tannins, which contribute to its broad pharmacological potential. Among these compounds, tannins play an important role in various therapeutic applications such as hemostasis, burn treatment, and the management of diarrhea, dysentery, and tumors. In addition, tannins possess anticholesterol properties by precipitating mucosal proteins on the surface of the small intestine, thereby reducing the absorption of cholesterol and lipids into the bloodstream. This study aimed to determine the tannin content in the ethanol extract of Bajakah Tampala root as part of an investigation into its potential as a natural anticholesterol agent. The extraction process was carried out using the maceration method with 96% ethanol as the solvent to ensure efficient recovery of phenolic compounds. Quantitative analysis of tannin content was performed using the UV-Visible spectrophotometric method at a wavelength of 750 nm, with gallic acid employed as the standard reference compound. The results showed that the tannin concentration in the ethanol extract of Bajakah Tampala root was 91.699 mg GAE/g extract (milligrams of gallic acid equivalent per gram of extract). These findings suggest that Bajakah Tampala root possesses a high tannin content, supporting its potential development as a natural anticholesterol agent and contributing to the growing evidence of its pharmacological benefits in traditional medicine.